Analysis of Tilapia (Oreochromis niloticus) Production Management at the Freshwater Fish Seed Center, Bontomanai Village, Bontomarannu District, Gowa Regency - Irawati, Arwita Ira; Azizah, Wafiq (Jurnal Salamata, 2025)
One of the areas for the development of Nile fish cultivation activities is the Fish Seed Center in Bontomarannu District, Bontomanai Village, Gowa Regency. The potential in this area is very high due to geographical, social, and demographic factors. This study aims to understand the application of management functions in Nile fish production at the Fish Seed Center conducted by the respondents. This research was conducted from March to April 2025. The collected data includes observations, namely direct observations at the Freshwater Fish Seed Center, covering activities from breeding, maintenance, to the distribution of tilapia. This is followed by direct interviews with involved parties such as the head of the center and field staff, which are then analyzed descriptively qualitatively. The research results show that the Production Management at the Bontomanai Fish Seed Center is performed well and is based on several stages including the receipt of raw materials, pond construction, land preparation, and harvesting. The planning conducted includes the drying of the base soil, processing of the base soil, pond embankment, pond depth, liming, fertilizing, filling water, selecting Nile Tilapia broodstock, spawning the broodstock, mass spawning, harvesting, and marketing. In terms of organizing function, detailed tasks have been outlined for each existing worker. The supervision process is carried out in feeding and monitoring for diseases.